2014
DOI: 10.3892/mmr.2014.2544
|View full text |Cite
|
Sign up to set email alerts
|

Taurine supplementation reduces oxidative stress and protects the liver in an iron-overload murine model

Abstract: We previously demonstrated that iron overload induces liver damage by causing the formation of reactive oxygen species (ROS). Taurine is a potent free radical scavenger that attenuates the damage caused by excessive oxygen free radicals. Therefore, the aim of the present study was to investigate whether taurine could reduce the hepatotoxicity of iron overload with regard to ROS production. Mice were intraperitoneally injected with iron 5 days/week for 13 weeks to achieve iron overload. It was found that iron o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 45 publications
4
58
0
1
Order By: Relevance
“…The antioxidant effects attributed to TAU may be associated with its sulfur moiety, and the modulation of GSH and GSH levels by TAU is critical in the cellular defence against oxidative stress. Consistent with the antioxidant properties of taurine observed in the present study [55], also found protective role of TAU on hepatocytes subjected to ironoverload as a way of oxidative stress.…”
Section: Discussionsupporting
confidence: 93%
“…The antioxidant effects attributed to TAU may be associated with its sulfur moiety, and the modulation of GSH and GSH levels by TAU is critical in the cellular defence against oxidative stress. Consistent with the antioxidant properties of taurine observed in the present study [55], also found protective role of TAU on hepatocytes subjected to ironoverload as a way of oxidative stress.…”
Section: Discussionsupporting
confidence: 93%
“…[49] Also, Hepatoprotective feature of taurine is attributed to its inhibitory activity on generation of ROS. [50] In the current work, administration of taurine not only effectively inhibited thioacetamide-induced hepatic encephalopathy, but also it has a great effect on serum, liver and brain ammonia as well as inflammatory cytokines (IL-1β, IL-6 & TNF-α) (Tables 2-5). Taurine might inhibit thioacetamide bioactivation through CYP2E1inhibition and consequently prevent hepatic injury.…”
Section: World Journal Of Pharmacy and Pharmaceutical Sciencesmentioning
confidence: 63%
“…Some osmoprotective amino acids are known to possess antitoxic properties (Yancey 2005;Graf et al 2008;Adamian et al 2012), and their protective mechanisms are mostly associated with alleviation of oxidative stress (Zhang et al 2014). Taurine and hypotaurine, which are amino acids synthesised and accumulated in mammalian reproductive fluids, were found to strong antioxidants scavenging OH and HOCl radicals protecting sperm and eggs (Welborn and Manahan 1995;Aruoma et al 1988;Schaffer et al 2003).…”
Section: Discussionmentioning
confidence: 99%